2013
DOI: 10.3233/nre-130911
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of electrical stimulation of the neurogenic bladder: Results of a two-year follow-up study

Abstract: INTRODUCTION:The complications of neurogenic dysfunction of the urinary bladder still constitute an important cause of death among spinal cord injury patients. AIM OF STUDY: The aim of this study was to assess transcutaneous electrical stimulation of the urinary bladder as a treatment for micturition disorders in patients after spinal cord injury (SCI) over 2 years of follow-up. MATERIAL AND METHODS:The study involved 28 patients (22 men and 6 women) with neurogenic bladder dysfunction following a spinal cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…To our knowledge few studies have been performed to determine the effects of PTNS on NDO in patients with MS. Acute urodynamic effects of PTNS in NOAB were studied with different neurological disorders including MS, spinal cord injury, and PD . In our previous studies we reported the effects of PTNS with acute urodynamic parameters on NDO in MS and PD patients and we found an increase of first involuntary detrusor contraction volume and of cystometric capacity with NOAB patients .…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge few studies have been performed to determine the effects of PTNS on NDO in patients with MS. Acute urodynamic effects of PTNS in NOAB were studied with different neurological disorders including MS, spinal cord injury, and PD . In our previous studies we reported the effects of PTNS with acute urodynamic parameters on NDO in MS and PD patients and we found an increase of first involuntary detrusor contraction volume and of cystometric capacity with NOAB patients .…”
Section: Discussionmentioning
confidence: 93%
“…Typically, patients suffer from an inability to fully void the bladder, which can lead to severe complications including kidney failure (Krause et al, 2004; Biering-Sørensen et al, 2008). Non-invasive DC modulation of the spinal cord has had some success restoring micturition function in humans (Flamm et al, 1977; Radziszewski, 2013; Stewart et al, 2016; Zhu et al, 2016). The mechanism of action is thought to be subthreshold modulation of spinal circuits rather than the result of DC-evoked spike trains (Kerns et al, 1996; Ahmed and Wieraszko, 2012; Ahmed, 2013, 2017).…”
Section: Potential Applications For DC Modulationmentioning
confidence: 99%
“…DC delivery closer to the target tissue could improve effect thresholds and reduce current spread to non-target tissues. Additionally, non-invasive DC still must contend with toxic electrochemical reactions generated at the metal-electrolyte interface, and is typically only delivered therapeutically for relatively short periods (Radziszewski, 2013). An implantable system capable of delivering chronic DC could provide tonic active therapy for cases where short-duration therapy is not efficacious.…”
Section: Potential Applications For DC Modulationmentioning
confidence: 99%
“…TESS has shown improvements in sensory and motor function when it is applied alone or in combination with other therapies (Hofstoetter et al, 2013;Gerasimenko et al, 2015;Gad et al, 2017Gad et al, , 2018Inanici et al, 2018). Improved cardiovascular (Phillips et al, 2018) and bladder (Horst et al, 2013;Radziszewski, 2013) functions and reduced spasticity (Hofstoetter et al, 2014(Hofstoetter et al, , 2020 have also been observed. While it is clear that single TESS pulses generate spinally mediated responses activating spinal networks that project transsynaptically to motoneurons (Milosevic et al, 2019), the effects of repeated use of TESS on CNS pathways remain unknown.…”
Section: Introductionmentioning
confidence: 98%